HASAN AL-BANNA (Problematika Islam Mesir dan Da’wah) - Masnur Kasim (Lembaga penelitian dan pengabdian kepada masyrakat, 2010)
During the early 1800s, Egyptian cotton exporting cotton in large quantities and eventually became the main results of Egypt. To facilitate the growth of trade between Egypt and Europe, foreign investors support a variety of projects to develop communication and modern transportation infrastructure. Egypt, after successfully controlled by Napoleon of France in the 19th century Egyptian natural resources exploited by the imperialists during this century, the fate of Economics and Political of egypt getting pinched